PMMA Microfiber And Microball Resonator For Fomaldehyde Liquid Sensing - Md Johari, Md Ashadi; Mat Sharif, Maslinda; Al Noman, Abdullah; Harun, Sulaiman Wadi; Abdul Khudus, Muhammad Imran Mustafa (Elsevier B.V., 2020)
This experiment reports the fabrication of the Polymethyl Methaclyrate (PMMA) Microball Resonator (MBlR) as a liquid sensor tested on various level of concentration of the Formaldedhye liquid. The PMMA MBlR is fabricated via the “dipped and twirl” method to create the sphere-shaped ball with diameter Db = 320um. The MBlR is then optically excited using a 9 μm PMMA microfiber and was found to have a Q Factor of >104. The MBlR was then employed as a liquid sensor with the level percentage range between 0%–4% of Formaldehyde liquid and the performance is compared with a non MBlR microfiber. The MBlR sensor was found to have a sensitivity of 6.94 dB m/%, linearity >90 % and P-value of more than 105. The PMMA MBlR liquid sensor was also found to have a good repeatability and stability over a period of 60 s.